Reimagining rewilding: A response to Jørgensen, Prior, and Ward. (November 2016) - Cloyd, Aaron A.
Highlights: Jørgensen's, Prior's, and Ward's rewilding conversation is continued and expanded. Feldman's work expands a focus on European geographies. Two fictional works expand research to include the humanities. Empathy is given as a reason to include imaginary writings in rewilding debates. Abstract: This article continues and expands the conversation initiated by Jørgensen on the need to rethink rewilding, which elicited a response from Prior and Ward. To spur further conversation, my response to both papers argues for two modes of discourse expansion: geographical and disciplinary. Although both articles gesture toward global rewilding sites, their discussions remain focused on European geographies. I offer James Feldman's environmental history of the Apostle Islands to extend a geographical purview beyond European contexts. Secondly, I take up these papers' implicit call for humanities scholars to join this conversation, and I argue for the relevance and importance of fictional writings to a debate regarding rewilding. I briefly introduce two recent fictional works and argue for their place in rewilding conversations based on the ability of imaginary writings to develop empathy.